Internet Access and Internet Self-efficacy of High School Students - Wayan Suana; Afif Rahman Riyanda; Ni Made Anggi Arlina Putri (Journal of Educational Science and Technology (EST), 2019)
This study aimed at determining the availability of the internet facility, access, and internet usage in general as well as in learning physics among high school students in Lampung, Indonesia. The study also assessed students’ internet self-efficacy and perception of the internet in learning physics. A number of 1883 students, which consists of 700 males and 1183 females, participated in this descriptive study. A questionnaire consisted of 30 items was implemented in this study. The results showed that most students have internet facilities and nearly all of them have internet access through mobile phones. The majority of students had used the internet for more than or equal to three years (78.1%). In using the internet, students have two main reasons, for academic purposes (90.3%) and for social media activities (89.5%). Majority of internet service used in physics was to solving homework (78.5%). The study also revealed that students’ internet self-efficacy and perception for learning physics were in “high” and “positive” category, respectively. These results imply that the students’ internet facilities, access, experience, and self-efficacy are categorized high. Therefore, the integration of internet in teaching physics at high school in Lampung is adequately potential.